ANALISIS DETERMINAN INTENSITAS PENGGUNAAN PROGRAM BANTUAN KESEHATAN (BK) DI KECAMATAN SUKAWATI, KABUPATEN GIANYAR - Pramesti, Ni Luh Ayu Kristi; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023DO - 10.24843/EEB.2023.v12.i03.p12, 2023)
Bantuan Kesehatan Program is a free health insurance financing program for resident of Gianyar Regency who do not have access to health insurance. The research location is in Sukawati District, Gianyar Regency. The type of data used is quantitative data with primary data sources. The sample size was calculated using the Slovin formula with a total of 100 respondents using the BK Program. The method of determining sample is simple random sampling, with data collection methods of observation, in-depth interviews, and structured interviews using a questionnaire instrument. The data analysis technique used descriptive statistical analysis and path analysis. The results showed that age, education and number of family dependents had a positive and significant effect on family income. Age and number of family dependents had a positive and significant effect on the intensity of using the BK Program. Education and family income had a negative and significant effect on the intensity of using the BK Program. Family income mediate the effect of age, education, and number of family dependents on the intensity of using the BK Program.